2009
DOI: 10.1258/rsmsmj.54.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Acute Caffeine Ingestion: Clinical Features in Patients Attending the Emergency Department and Scottish Poison Centre Enquiries Between 2000 and 2008

Abstract: Caffeine ingestion is uncommon, and results in only a small number of hospital attendances and Poisons Centre enquiries. In contrast to patterns reported elsewhere, the prevalence of caffeine abuse has not increased in Scotland over recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…The recreational abuse of caffeine seems to vary by region; a recent report from Scotland suggests that the abuse has remained constant over recent years. 2 Whereas a report from United States considers a rising occurrence of caffeine abuse and regards any attempt to prevent abuse as very difficult. 3 Numerous toxic effects of caffeine have been described.…”
Section: Introductionmentioning
confidence: 99%
“…The recreational abuse of caffeine seems to vary by region; a recent report from Scotland suggests that the abuse has remained constant over recent years. 2 Whereas a report from United States considers a rising occurrence of caffeine abuse and regards any attempt to prevent abuse as very difficult. 3 Numerous toxic effects of caffeine have been described.…”
Section: Introductionmentioning
confidence: 99%
“…[41] Caffeine can, potentially, cause significant acute toxicity, [42] and there is the potential that the caffeine found in products containing DMAA may contribute to the toxicity associated with their use. [41] Caffeine can, potentially, cause significant acute toxicity, [42] and there is the potential that the caffeine found in products containing DMAA may contribute to the toxicity associated with their use.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of large amounts of caffeine can cause significant agitation, severe hypotension, tachycardia, ventricular arrhythmia, cardiac arrest, myocardial infarction, hypokalemia, rhabdomyolysis, seizures and acute renal impairment 8,9 . Waring et al 10 showed clinical data of 38 patients with caffeine ingested at an average dose of 1,040 mg (600 to 1,500 mg), which is equivalent to the amount found in about 10 cups of coffee. Out of them, 28 (73.7%) patients attempted suicide by deliberate self-poisoning, 8 (21.1%) patients ingested caffeine in order to enjoy (energy drinks), and 2 (5.3%) patients did it for weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…The presented patient was anxious upon admission, and later complained of a headache. According to the Scottish Poison Centre (for the period 2000 -2008) dizziness, headache, tremor and agitation were much less common symptoms of caffeine poisoning in comparison to those with gastrointestinal symptoms 10 .…”
Section: Discussionmentioning
confidence: 99%